A Decision Making Approach for Automobile Selection Based on TOPSIS - Ergül, Sezin Güleryüz; Çokyaşar, Aysel (Osman SAĞDIÇ, 2021)
Individuals or companies evaluate and analyze too many alternatives and criteria when choosing. While making these decisions, they can make scientific, successful and acceptable decisions by using multi-criteria decision-making techniques. In multi-criteria decision making problems, a certain number of alternatives are compared and ranked. The best is tried to be selected by using scientific methods.Today, industrial, financial and economic decision problems are multi-criteria. With the technology renewed every day, automobile manufacturers offer a wide variety of models and alternatives to consumers. Consumers do not only look at the brand or price when buying a car. It is effective in choosing criteria such as fuel, performance and design. But the optimal choice of each consumer differs. For some, fuel economy is a high criterion, while for others, design and equipment purchase can also be decisive. In this study, TOPSIS (Technique for Order Preference by Similarity to Ideal Solutions) method, which is one of the Multi-Criteria Decision Making (MCDM) techniques aims to help consumers make their choices while purchasing a car. The originality of the study is due to the application of the TOPSIS method, which is frequently used in the literature, with a real case.

Kişiler ya da şirketler seçim yaparken çok fazla alternatif ve kriterleri değerlendirip analiz eder. Bu kararları verirken çok kriterli karar verme (ÇKKV) tekniklerinden yararlanarak bilimsel, doğru ve kabul edilebilir kararlar oluşturabilirler. ÇKKV problemlerinde belirli sayıda alternatifler karşılaştırılarak derecelendirilir. Bilimsel yöntemler kullanılarak en iyisi seçilmeye çalışılır. Günümüzde endüstriyel, finansal ve ekonomik karar problemleri çok kriterli yapıdadır. Her gün yenilenen teknoloji ile otomobil üreticileri, tüketicilere çok çeşitli model ve alternatif sunmaktadır. Tüketiciler otomobil satın alırken sadece markasına ya da fiyatına bakmazlar. Yakıt, performans, tasarım gibi kriterlerde seçim yapmada etkilidir. Fakat her tüketicinin optimal seçeneği farklılık göstermektedir. Kimine göre yakıt tasarrufu yüksek kriter olurken, kimine göre ise tasarım ve donanım satın alma da belirleyici olabilir. Bu çalışmada ÇKKV yöntemlerinden TOPSİS (Technique for Order Preference by Similarity to Ideal Solutions) tekniği kullanılarak tüketicilerin otomobil satın alırken seçimlerine yardımcı olmayı amaçlamaktadır. Çalışmanın özgünlüğü, literatürde sıklıkla kullanılan TOPSIS yönteminin gerçek bir olayla uygulanmasından kaynaklanmaktadır.
Otomobil Seçimi İçin TOPSIS Temelli Bir Karar Verme Yaklaşımı
Keywords: Engineering; Mühendislik